1983
DOI: 10.3758/bf03203049
|View full text |Cite
|
Sign up to set email alerts
|

Memory and preference for the colors of objects

Abstract: Memory for object color often produces object-specific deviations from actual color. Several studies have indicated that "memory colors" exist and in some cases influence perception of object color. Systematic changes in memory for color per se cannot account for these memorycolor phenomena. A study was conducted to characterize more specifically the nature of memory for object color information. The study was designed to assess the dependence of memory color on shape and texture information, to compare memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
68
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 16 publications
13
68
0
2
Order By: Relevance
“…They also found that hue shifts were reduced by increasing the naturalness of the stimuli. Siple and Springer [6] confirmed the tendency for saturation increase, but reported quite accurate agreement for brightness and hue. In a study by Pérez-Carpinell, de Fez, Baldoví and Soriano [7] memory saturation only increased for high purity objects, while it decreased or remained the same for midrange or low purity objects.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…They also found that hue shifts were reduced by increasing the naturalness of the stimuli. Siple and Springer [6] confirmed the tendency for saturation increase, but reported quite accurate agreement for brightness and hue. In a study by Pérez-Carpinell, de Fez, Baldoví and Soriano [7] memory saturation only increased for high purity objects, while it decreased or remained the same for midrange or low purity objects.…”
Section: Introductionmentioning
confidence: 72%
“…Studies on preferred object colors have also reported saturation increases with respect to the actual object colors [6,[9][10][11][12]. The preferred color of an object is not necessarily identical to its memory color [13], although Siple and Springer [6] could not identify any significant differences between memory and preferred colors for food objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siple & Springer [9] used a colorimeter and controlled photographs of six fruits and vegetables to study the memory color and preference for them when presented with and without context. Although they also obtained simultaneous matches using the photographs and real fruit as references the memory matches were obtained before participants had seen this particular version of the objects so they were based on some previous internal representation.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of deviation between the rendered image and the undistorted original is often used as a measure for image quality. Such an approach, however, cannot describe situations in which the original image does not possess the highest quality, as found by amongst others Hunt (1982) 1 and Siple and Springer (1983). 2 In such situations, image quality should be predicted from the rendered image only.…”
Section: Introductionmentioning
confidence: 99%